Report of the Committee of Elections upon the resolution of Mr. Wysor in regard to absent members (LLMC-digital (Series), 1861)
Contains the report of the Committee of Elections regarding the Mr. Wysor's resolutions dealing with absent members. The committee investigated and determined which members of the Convention were "aiding and abetting the open enemies of Virginia;" these seats were declared vacant and no pay would issue for their services.